PENGARUH PENINGKATAN SDM APARATUR PEMERINTAH TERHADAP KUALITAS PELAYANAN KTP DI KECAMATAN BATU MARMAR KABUPATEN PAMEKASAN - Cahyo Sasmito (REFORMASI, 2012)
That deep Observational about SDM'S Step-up Influence Government Apparatus to KTP'S Ministering quality At Batumarmar's district this Pamekasan's Regency at knows that SDM Berpenggaruh Signifikan's Step-up to ministering quality,or there is influence relationship that signifikan among Sistim's Purpose variable demography Administration Information (SIAK) on-line and variable Apparatus Human Resource quality to Ministering quality variable KTP at Batumarmar's district Pamekasan's Regency. Thus SDM is agency shall can utilize information technology corresponds to what do be wanted by organization in order to render that organization aim, so apparatus behaviour and service form that gave by organization to society can correspond to that desirable by public that. tehnologi's mastery combine information and SDM IS agency precisely deep ministering public will really help deep regard public service quality.